The Wilson's disease - etiology, symptoms in various organs, diagnosis, treatment, prognosis - Patryk Graczyk; Paulina Klaudia Kwaśniewska; Anna Wilewska; Kinga Borowiec; Agnieszka Borowiec; Julia Biernikiewicz; Konstanty Alabrudziński; Milena Biernikiewicz; Bartosz Pomirski; Agata Pomirska (Journal of Education, Health and Sport)
Introduction: